1976
DOI: 10.1073/pnas.73.12.4339
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cell surface glycosphingolipids and other lipid classes of fibroblasts in familial hypercholesterolemia.

Abstract: The glycosphingolipids (GSL) and other major lipid classes were studied in cultured fibroblasts from a family with familial hypercholesterolemia. The GSL content in cells grown in medium containing fetal calf serum was increased 5-fold in the homozygote and 2-to 3-fold in both heterozygous parents. Cell surface labeling experiments, using the membrane probe galactose oxidase followed by reduction with KB3H4, showed an increased incorporation of 3H by the homozygous cells into GL4 (4-fold), GM3 (2-to 3-fold), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…11 LacCer is a ubiquitous glycosphingolipid and plays a pivotal role in the biosynthesis of complex glycosphingolipids (16). Moreover, LacCer may contribute to proliferative diseases such as polycystic kidney disease, atherosclerosis (17), and familial hypercholesterolemia (18,19). The biological function of LacCer was illustrated previously with two examples.…”
Section: Laccer Stimulates the Adhesion Of Neutrophils Tomentioning
confidence: 99%
See 2 more Smart Citations
“…11 LacCer is a ubiquitous glycosphingolipid and plays a pivotal role in the biosynthesis of complex glycosphingolipids (16). Moreover, LacCer may contribute to proliferative diseases such as polycystic kidney disease, atherosclerosis (17), and familial hypercholesterolemia (18,19). The biological function of LacCer was illustrated previously with two examples.…”
Section: Laccer Stimulates the Adhesion Of Neutrophils Tomentioning
confidence: 99%
“…LacCer is also elevated in atherosclerotic plaque intima (20,21) and in patients with familial hypercholesterolemia (18,19), it is tempting to speculate that this GSL may serve as a lipid second messenger that may be required to stimulate O 2 . generation and ICAM-1 expression in atherosclerosis.…”
Section: Laccer Stimulates the Adhesion Of Neutrophils Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has reported a close relationship between increased levels of LacCer and hyperproliferation in diverse human diseases. For example, in human atherosclerotic plaque (6), familial hypercholesterolemia (36,37), and human polycystic kidney disease, an increased cellular/tissue level of LacCer was accompanied by cell hyperproliferation (38). Among several GSLs investigated, we found that LacCer exerts the highest stimulation in H-ASMC proliferation (1), and LacCer from human atherosclerotic plaque tissue was significantly more effective in stimulating H-ASMC proliferation than LacCer from the unaffected aorta (6).…”
Section: Effect Of Nac Bso and Dpi On Laccer-induced C-fosmentioning
confidence: 99%
“…Our previous work in cultured fibroblasts indicated that there was an alteration of GSL metabolism in certain FH receptornegative homozygotes (4,5). Recently, Verdery and Theolis (6) showed that the synthesis of sphingosine, a long-chain base and a precursor of the ceramide component of GSL, was inhibited by LDL in cultured human fibroblasts.…”
mentioning
confidence: 99%